Aktivitas Ekonomi Komunitas di Indonesia : Kajian Terhadap Kontibusi Social Capital - Ahmad Sukron; Adellia Saniyatuz Zahro (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak: This study aims to analyze and understand the role of social capital in driving community economic activity in Indonesia. Social capital is seen as a crucial factor in building community economic independence through trust, social networks, and local norms that support productive cooperation. This study employed a qualitative method with a library research approach, analyzing various books, journal articles, and relevant research reports. The results indicate that social capital functions as social infrastructure that strengthens community-based economic activity. Social networks play a role in facilitating information exchange and resource access, while trust and norms serve as productive capital that lowers social transaction costs and strengthens long-term economic collaboration. Local values ​​such as mutual cooperation, deliberation, and social solidarity have been shown to be the moral foundation for community economic sustainability. This study concludes that strengthening social capital, supported by socio-economic literacy and the use of digital technology, can be an effective strategy for creating sustainable, inclusive, and equitable economic development at the community level.